The FDA's New Guideline "Generally Accepted Scientific Knowledge" (GASK): An Opportunity to Expedite the Approval of Biosimilars - Sarfaraz K. Niazi (MDPI AG, 2023)
The US FDA's new guideline suggests using "Generally Accepted Science Knowledge" (GASK) to develop nonclinical testing protocols for developing drugs and biologicals to remove unnecessary testing. Interpreting acceptable scientific knowledge as a rational approach has motivated the author to suggest substantial changes to the development of biosimilars, as demonstrated in this paper. The FDA can accept these suggestions without requiring any legislative change to the Act that defines such requirements. Suggested here is the waiving of clinical efficacy testing due to its lower sensitivity compared to analytical and functional testing and pharmacokinetic profiling. Also questioned is the need to test pharmacodynamic markers that do not correlate with clinical response and find new biomarkers requiring extensive testing to validate their use. Should the FDA accept these scientifically rational suggestions, it will significantly reduce the time and cost of approving biosimilars without safety or efficacy risk, as justified based on acceptable scientific knowledge and rationality.